Clinical and Laboratory Aspects of Disseminated Intravascular Coagulation (DIC): A Study of 118 Cases - Siegal, Tali; Seligsohn, Uri; Aghai, Esther; Modan, Michaela (Thrombosis and Haemostasis, 1978)
The medical records of 118 cases who met laboratory criteria of DIC were studied. The most frequent etiologies were: Generalized infection (39.8%), trauma (16.9%), malignancy (6.8%) and surgical cases (6.8%). The main clinical manifestations which appeared to be related solely to DIC were (in a decreasing order of frequency): Bleeding (64.4%), renal dysfunction (24.6%), liver dysfunction (18.6%), respiratory dysfunction (16.1%), shock (14.4%), thromboembolic phenomena (6.8%) and central nervous system involvement (1.7%). In 26 patients none of these manifestations were observed. In patients with infection, liver and renal dysfunction were frequent and respiratory dysfunction rare, whereas in trauma cases, liver and renal dysfunctions were rare and respiratory dysfunction frequent. This variability indicates that the clinical manifestations are affected not only by the process of intravascular coagulation but also by the underlying clinical disorders.The most impaired coagulation tests were prothrombin time, partial thromboplastin time, platelet count and thrombin time. The degree of abnormality of these coagulation tests was found to be related to the extensiveness of organ involvement.The mortality (overall 54.7%) increased independently with age, with the number of clinical manifestations and with the degree of abnormality of the above-mentioned four most impaired coagulation tests. In addition, older patients were more likely to have an increased number of clinical manifestations and more impaired coagulation tests. Mortality was similar in the various etiologies except for trauma patients in whom it was lower (30%).